ANALISIS COST VOLUME PROFIT SEBAGAI DASAR PERENCANAAN LABA PERUSAHAAN YANG DIHARAPKAN - Simon, Alex; Septiana, Tian; Suci, Rama Gita (Research in Accounting Journal (RAJ), 2021)
A company needs planning to assist management in estimating the level of profit to be obtained, with a Cost-Volume-Profit analysis that focuses on various factors that influence changes in the earnings component. This study aims to determine the application of CVP analysis as a basis for expected earnings planning for the second quarter of 2020. The method used is a descriptive method with a case study approach. Researchers gather company information and then conduct data analysis. CVP analysis is performed with break event point (BEP) analysis, contribution margin, and margin of safety. The results showed that in the first quarter the contribution margin was IDR 32,424,125. The minimum sales are IDR 19,330,018 and the break-even point is IDR 39,838,182. The company set a profit of 20% from the first quarter. To achieve the expected profit, sales are targeted at Rp. 62,775,909 in the second quarter. Management can apply CVP analysis to assist in planning earnings in the following quarter.